Competitive multicomponent anion exchange adsorption of proteins at the single molecule level. Issue 17 (26th July 2017) - Kisley, Lydia; Patil, Ujwal; Dhamane, Sagar; Kourentzi, Katerina; Tauzin, Lawrence J.; Willson, Richard C.; Landes, Christy F.
Abstract : Super-resolution imaging of multicomponent, competitive adsorption demonstrates that competitors block certain ligands from the analyte without changing analyte adsorption kinetics. Abstract : We use single molecule spectroscopy to study a multicomponent, competitive protein adsorption system. Fluorescently-labeled α-lactalbumin proteins are super-resolved adsorbing to cationic anion-exchange ligands in the presence of a competitor, insulin. We find that the competitor reduces the number of binding events by blocking ligands throughout the observed measurement time while the single-site adsorption kinetics are unchanged.